Changes in the Meaning of Foreign Languages, Regional Languages and Similar Languages in Indonesian Language - Sulaeman, Agus; Hun, Kim Dong (STIBA IEC JAKARTA, 2025)
This study analyzes the phenomenon of vocabulary shift in Indonesian, which originates from three main elements: foreign languages, regional languages, and cognate languages. The focus of the study lies in the sociolinguistic relationship between the language-speaking community and this expansion. The research method uses a descriptive-qualitative approach with data drawn from various sources such as mass media, literature, and everyday conversation. The results of the analysis show that vocabulary expansion from foreign languages is often triggered by globalization and technological developments, while the expansion of the language itself reflects the language's creativity in responding to local cultural needs. On the other hand, contributions from cognate languages such as Malay appear more in the context of cultural and historical similarities. This study concludes that language expansion is influenced by social, cultural, and economic dynamics, while also demonstrating that language plays a role as a mirror of societal change. The study of changes in meaning shows that the development of Indonesian not only enriches vocabulary but also reflects the social, cultural, and technological dynamics in society.